Dendrimer‐Based Nanosensitizers: Targeted Tumor Hypoxia Dual‐Mode CT/MR Imaging and Enhanced Radiation Therapy Using Dendrimer‐Based Nanosensitizers (Adv. Funct. Mater. 13/2020). (26th March 2020) - Fan, Yu; Tu, Wenzhi; Shen, Mingwu; Chen, Xuming; Ning, Yuesheng; Li, Junjun; Chen, Tingfeng; Wang, Han; Yin, Fangfang; Liu, Yong; Shi, Xiangyang
Abstract : In article number 1909285, Yong Liu, Xiangyang Shi, and co‐workers report hypoxia‐targeted dendrimer‐based nanodevices, which can be employed as a contrast agent for dual mode CT/MR imaging of hypoxic tumors. Moreover, under X‐ray irradiation, the developed nanohybrids enable enhanced reactive oxygen species production, promote DNA damage, and prevent DNA repair, facilitating sensitized radiotherapy of hypoxic tumors in vivo.